1’- Acetoxychavicol acetate Suppresses Osteosarcoma Cell Proliferation through the PI3K Pathway: A Molecular Docking and Cytotoxicity Study - Safitri, Putri Gita Ayu; Da’i, Muhammad; Wulandari, Febri (Molecular and Cellular Biomedical Sciences, 2025)
Background: This study aims to investigate anticancer properties of 1'-Acetoxychavicol acetate (ACA), a phenylpropanoid substance obtained from the rhizomes of the Alpinia genus, which has been extensively studied. However research on its cytotoxic effects, particularly against osteosarcoma cells, has never been donenot been conducted. The purpose of the research is to investigate the anticancer potential of ACA to support the its development as a novel therapeutic candidate.Materials and methods: This study assessed ACA’s initial anticancer potential through in vitro cytotoxic tests on normal human osteoblast cells (hFOB) and osteosarcoma cells (MG-63) using the MTT assay. Additionally, bioinformatics analyses, including target prediction, gene ontology, hub gene identification, protein-protein interactions (PPI) network construction, Kyoto encyclopedia of genes and genomes (KEGG) pathways analysis, disease association analysis, and molecular docking, were performed. Results: The cytotoxicity test on normal hFOB showed an IC50 of 45.05 µM, while in MG-63 osteosarcoma cells, the IC50 was 20.41 µM. In the bioinformatics test, top five target genes identified were SRC, GNAI1, PIK3CD, PIK3CB, PIK3R3. Molecular docking analysis showed that, the native PI3KD ligand showed a strong binding affinity of -10.99 kcal/mol and interacted with more amino acid residues.Conclusion: Overall, ACA exhibits promise as a treatment option to inhibit osteosarcoma cell proliferation by targeting the PI3K pathway. To develop ACA as a potential osteosarcoma therapeutic candidate, extensive in vitro research is needed.   Keywords: 1-Acetoxychavicol acetate, bioinformatics, cytotoxicity, osteosarcoma, PI3K pathway